Mitochondrial inhibitory factor 1 (IF1) is present in human serum and is positively correlated with HDL-cholesterol. - Annelise Genoux (Public Library of Science (PLoS), 2011)
Background Mitochondrial ATP synthase is expressed as a plasma membrane receptor for apolipoprotein A-I (apoA-I), the major protein component in High Density Lipoproteins (HDL). On hepatocytes, apoA-I binds to cell surface ATP synthase (namely ecto-F(1)-ATPase) and stimulates its ATPase activity, generating extracellular ADP. This production of extracellular ADP activates a P2Y(13)-mediated HDL endocytosis pathway. Conversely, exogenous IF1, classically known as a natural mitochondrial specific inhibitor of F(1)-ATPase activity, inhibits ecto-F(1)-ATPase activity and decreases HDL endocytosis by both human hepatocytes and perfused rat liver. Methodology/principal findings Since recent reports also described the presence of IF1 at the plasma membrane of different cell types, we investigated whether IF1 is present in the systemic circulation in humans. We first unambiguously detected IF1 in human serum by immunoprecipitation and mass spectrometry. We then set up a competitive ELISA assay in order to quantify its level in human serum. Analyses of IF1 levels in 100 normolipemic male subjects evidenced a normal distribution, with a median value of 0.49 µg/mL and a 95% confidence interval of 0.22-0.82 µg/mL. Correlations between IF1 levels and serum lipid levels demonstrated that serum IF1 levels are positively correlated with HDL-cholesterol and negatively with triglycerides (TG). Conclusions/significance Altogether, these data support the view that, in humans, circulating IF1 might affect HDL levels by inhibiting hepatic HDL uptake and also impact TG metabolism.